Smart Village "Let's Open a Window on the World by Reading Books" Desa Cerdas “Ayo Kita Membuka Jendela Dunia Dengan Membaca Buku” - Oci Senjaya*; Imam Budi Santoso; M.Reza Pahlevi (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2023)
The School Literacy Movement is a program from the Ministry of Education and Culture. As the general aim of the School Literacy Movement is to develop the character of students through cultivating the school literacy ecosystem which is manifested in the School Literacy Movement so that they become lifelong learners. The School Literacy Movement program is implemented through 3 stages, namely the habituation stage, the development stage, and the learning stage. Currently, students' literacy skills are still low. This can be seen from the activities of students who prefer playing gadgets rather than reading books or other reading. In addition, students tend to ask questions before reading, even though the things asked have been given complete information. Therefore, students' interest in reading needs to be increased, one of which is by developing a school literacy movement. Literacy ability is one of the competencies that students must have in the 21st century and will later be tested in the Minimum Competency Assessment (AKM). Therefore, in community service activities we want to foster a positive culture of fond of reading through the literacy movement in schools. With the above background we are interested in doing community service entitled: Smart Village "Let's Open a Window on the World by Reading Books" Keywords: Smart Village, Window on the World, Reading Books. Abstrak ß Cambria, Bold, 10 pt Gerakan Literasi Sekolah merupakan Program dari Kemendikbud Sebagaimana tujuan umum Gerakan Literasi Sekolah yaitu menumbuh kembangkan budi pekerti peserta didik melalui pembudayaan ekosistem literasi sekolah yang diwujudkan dalam Gerakan Literasi Sekolah agar mereka menjadi pembelajar sepanjang hayat. Adapun program Gerakan Literasi Sekolah diterapkan melalui 3 tahapan yaitu tahap pembiasaan, tahap pengembangan, dan tahap pembelajaran.Saat ini, kemampuan literasi siswa masih rendah. Hal tersebut dapat dilihat dari kegiatan siswa yang lebih gemar bermain gadget daripada membaca buku atau bacaan yang lainnya. Selain itu, siswa cenderung bertanya sebelum membaca, padahal hal yang ditanyakan sudah diberikan informasi secara lengkap. Maka dari itu, minat siswa dalam hal membaca perlu ditingkatkan, salah satunya dengan mengembangkan gerakan literasi sekolah. Kemampuan literasi merupakan salah satu kompetensi yang wajib dimiliki siswa pada abad 21 dan nantinya akan diujikan dalam Asesmen Kompetensi Minimal (AKM). Oleh karena itu, pada kegiatan abdimas ingin menumbuhkan budaya positif gemar membaca melalui gerakan literasi di sekolah.dengan latar belakang di atas kami tertarik untuk melakukan pengabdian masyarakat yang berjudul :Desa Cerdas”Ayo Kita Membuka Jendela Dunia Dengan Membaca Buku” Kata kunci: Desa Cerdas, Jendela Dunia, Membaca Buku.